Nemzetközi háttérszolgáltató szervezetek hálózati együttműködése - Marciniak Róbert (Taylor : gazdálkodás- és szervezéstudományi folyóirat, 2017)
This study aims to present the results of an ongoing international research project. The research aims to uncover the network operation of supporting service activities served centers of the multinational companies (commonly known as shared service centers) and explore the most important reasons behind the networking. The research is focused mainly on the Hungarian shared service market and its players that have strong relationship with other service centers operating in the Central and Eastern European countries. The research analyze why the parent companies operates several service centers in the same region, how are the services delivered distributed among the service centers, and are there any competition between these centers within the network, and how these service centers connect to the global operations of the parent companies.